2023
DOI: 10.3390/nu15122799
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Concentration of 51 Elements in the Liver and in Various Parts of the Human Brain—Profiling of the Mineral Status

Abstract: The anthropogenic environment and diet introduce many metals into the human body, both essential and toxic. Absorption leads to systemic exposure and accumulation in body fluids and tissues. Both excess and deficiency of trace elements are health hazards. The primary aim of the present study was to evaluate the concentration of 51 elements in liver samples and 11 selected brain regions obtained at post-mortem examination from a population of adults living in south-eastern Poland (n = 15). A total of 180 analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The sample preparation procedure was the same as previously published [51][52][53]. In brief, 7 mL of 69% suprapur nitric acid HNO 3 (Baker, Radnor, PA, USA) was added to approximately 0.3-0.5 g of tissue sample, followed by heating to 190 • C in closed Teflon containers in the microwave mineralisation system Multiwave 5000 (Anton Paar, Graz, Austria).…”
Section: Sample Mineralisationmentioning
confidence: 99%
“…The sample preparation procedure was the same as previously published [51][52][53]. In brief, 7 mL of 69% suprapur nitric acid HNO 3 (Baker, Radnor, PA, USA) was added to approximately 0.3-0.5 g of tissue sample, followed by heating to 190 • C in closed Teflon containers in the microwave mineralisation system Multiwave 5000 (Anton Paar, Graz, Austria).…”
Section: Sample Mineralisationmentioning
confidence: 99%
“…Another group showed that titanium content in mouse hippocampus after 90 days of continuous intranasal exposure to TiO 2 nanoparticles was 0.6 mg/g tissue at the highest administered dose of 10 mg/kg body weight (Ze et al, 2014), much higher than the levels observed in humans. Titanium can be found in human tissue at lower average concentrations ranging from 1 μg/g (Peters et al, 2020) up to 80 μg/g (Baj et al, 2023) in the human brain. Thus, neuroinflammation and impairment of spatial memory observed in mice occur at more than ten times higher brain content than observed in humans.…”
Section: Introductionmentioning
confidence: 99%